Leading Learning. - Stephenson, Lauren (BRILL, 2018)
In a world of constant change, the ongoing education and empowerment of women is a transformation of profound significance. In the UAE, and in Dubai in particular, the emergence of women into positions of leadership has accelerated over the past thirty years and continues to gather pace, reflecting a worldwide trend. Emirati women's entry into leadership positions in all fields has resulted in social and economic benefits across education, health, commerce and community services - all of which have strengthened the role of women at the grassroots level. As the world grows smaller, the global circle of opportunity for women grows wider. Throughout the UAE and all across the globe women are assuming their rightful place as leaders in education and in society. The authors conducted a ten-year collaborative narrative research project culminating in a book of jointly constructed stories of five exceptional female Emirati educational leaders. The five women from Dubai are Raja Al Gurg, Raya Rashid, Fatima Al Marri, Rafia Abbas, and Rashida Badri. Through stories of lived experience, this book recognizes the expertise and contributions of these women to the fields of education and leadership; provides exemplars for educators; demonstrates to younger generations what successes and challenges this generation of women faced in order to achieve recognition as successful women and members of the local, regional, and global community; and makes their leadership perspectives and experiences accessible and engaging for all types of audiences.